Exoesqueleto de membros inferiores para crianças com dificuldades de locomoção - Wahbe, Nadine Rubliauskas (2022)
Exoskeletons are promising technologies in rehabilitation medicine, since they help debilitated patients to improve their motor skills, thus increasing the quality of life of these individuals. Therefore, the objective of this work was to design and develop an adjustable, personalized and for locomotion assistance lower limb exoskeleton for children, based on the understanding of the neuromusculoskeletal system and the characteristics of human gait. Thus, the study of this robotic orthosis involved an investigation of existing technologies on the market, considering its applications, performance systems, available components, advantages and disadvantages. Then, a simulation of the actuation system in the open software Tinkercad was perfomed, with the purpose of controlling the gait time and obtaining a functional exoskeleton. Simultaneously, a mechanical structure of the device was modeled by Autodesk Inventor software to assist in physical construction and stress analysis. Finally, tests and a final assembly were performed, which consists of an adjustable exoskeleton with two degrees of freedom in a lower limb